2023
DOI: 10.1038/s41598-023-27792-0
|View full text |Cite
|
Sign up to set email alerts
|

FAT1 expression in T-cell acute lymphoblastic leukemia (T-ALL) modulates proliferation and WNT signaling

Abstract: FAT atypical cadherin 1 (FAT1), a transmembrane protein, is frequently mutated in various cancer types and has been described as context-dependent tumor suppressor or oncogene. The FAT1 gene is mutated in 12–16% of T-cell acute leukemia (T-ALL) and aberrantly expressed in about 54% of T-ALL cases contrasted with absent expression in normal T-cells. Here, we characterized FAT1 expression and profiled the methylation status from T-ALL patients. In our T-ALL cohort, 53% of patient samples were FAT1 positive (FAT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Here, using conditional knockout mice to eliminate Fat1 in HSCs, we show that Fat1 dispensable for haematopoiesis. This in turn infers that the prominent FAT1 expression in acute leukemias is an active oncogenic event, a notion supported by a recent study in T-ALL where many cases show FAT1 promotor hypomethylation [18]. From the broader perspective where Fat1 has often been linked with Hippo pathway regulation in different contexts [19], it is interesting to note that elimination of the Hippo effectors Yap and Taz was similarly dispensable for murine haematopoiesis [20].…”
Section: Resultsmentioning
confidence: 85%
“…Here, using conditional knockout mice to eliminate Fat1 in HSCs, we show that Fat1 dispensable for haematopoiesis. This in turn infers that the prominent FAT1 expression in acute leukemias is an active oncogenic event, a notion supported by a recent study in T-ALL where many cases show FAT1 promotor hypomethylation [18]. From the broader perspective where Fat1 has often been linked with Hippo pathway regulation in different contexts [19], it is interesting to note that elimination of the Hippo effectors Yap and Taz was similarly dispensable for murine haematopoiesis [20].…”
Section: Resultsmentioning
confidence: 85%
“…Several studies have reported a correlation of FAT1 mutation or expression with prognosis in various cancers, such as breast cancer, NSCLC, gastric cancer and T-cell lymphoma [40]. Positive correlation of FAT1 overexpression with proliferation and WNT/β-catenin signaling pathway in T-cell acute leukemia (T-ALL) is recently reported in a study [41]. ERG encodes a transcription factor involved in development and differentiation affecting vasculogenesis, haematopoiesis, angiogenesis and embryogenesis, and is associated with regulation of cellular processes [42].…”
Section: Discussionmentioning
confidence: 93%
“…A simple gesture, taking a small amount of blood or saliva for genetic typing, can save a life in the future. In addition to transplant surgery, other treatments today are chemotherapy combined with other approaches to stimulate the immune system to recognize and destroy leukemia cells [24][25]. It targets leukemia cells and promotes their destruction by the immune system.…”
Section: Introductionmentioning
confidence: 99%